2010
DOI: 10.1124/jpet.110.174821
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2Differentially Modulates Human Platelet Function through the Prostanoid EP2 and EP3 Receptors

Abstract: Activated human platelets synthesize prostaglandin (PG) E 2 , although at lower rate than thromboxane A 2 . PGE 2 acts through different receptors (EP1-4), but its role in human platelet function remains poorly characterized compared with thromboxane. We studied the effect of PGE 2 and its analogs on in vitro human platelet function and platelet and megakaryocyte EP expression. Platelets preincubated with PGE 2 or its analogs were stimulated with agonists and studied by optical aggregometry. Intraplatelet calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 43 publications
(78 reference statements)
1
34
0
2
Order By: Relevance
“…Our in vitro findings that EP3 receptor stimulation enhanced washed platelet aggregation and adhesion are in line with previous findings, showing an EP3-induced increase of agonist-induced aggregation in human whole blood and PRP [18,21,25] . In addition, we found that adhesion to fibrinogen and collagen under low flow conditions is enhanced based on EP3 receptor activation; however, whole blood thrombus formation on collagen under high flow was not significantly affected by the EP3 receptor agonist sulprostone.…”
Section: Discussionsupporting
confidence: 81%
“…Our in vitro findings that EP3 receptor stimulation enhanced washed platelet aggregation and adhesion are in line with previous findings, showing an EP3-induced increase of agonist-induced aggregation in human whole blood and PRP [18,21,25] . In addition, we found that adhesion to fibrinogen and collagen under low flow conditions is enhanced based on EP3 receptor activation; however, whole blood thrombus formation on collagen under high flow was not significantly affected by the EP3 receptor agonist sulprostone.…”
Section: Discussionsupporting
confidence: 81%
“…Previous research has identified that the effects of PGE 2 on platelet function are mediated mainly through interaction with the EP3 receptor, which promotes platelet function via a G i -linked mechanism, and through interaction with the EP4 receptor, which inhibits platelet function via a G s -linked mechanism [8][9][10][11][12][13][14]. In this study, we have examined the possibility that the action of PGE 2 at EP3 and EP4 receptors can explain the previous observation that this prostaglandin is able to reverse the inhibition of aggregation by agents that stimulate cAMP production via G s , but adds to inhibition provided by agents that raise cAMP through other mechanisms, including the inhibition of cAMP PDE and direct stimulation of adenylate cyclase [15].…”
Section: Discussionmentioning
confidence: 99%
“…Another naturally occurring prostaglandin, prostaglandin E 2 (PGE 2 ), is able to raise cAMP in a similar manner by interaction with the G s -linked EP4 receptor [9][10][11][12]. However, PGE 2 is unusual in that it also interacts with a second receptor, the G i -linked EP3, to inhibit adenylate cyclase [9,13,14]. Thus, PGE 2 has the ability to both inhibit and potentiate platelet function, the resultant effect depending on the concentration of the prostaglandin and the balance between its effects at both receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the anti-aggregatory role of EP2 and EP4 in murine or human atherothrombosis is currently unclear, making interspecies comparisons unreliable. Conversely, in both murine and human platelets, EP3 facilitates platelet aggregation [11-14, 16, 17, 19, 20, 31, 33] and sensitizes platelets by decreasing cAMP production, even when platelets are blocked by agents such as aspirin or clopidogrel [16,17,22] . Therefore, the signaling pathway activated by EP3 translates well from murine to human platelets and, as in mice, PGE2 does facilitate the human platelet response by activating its receptor EP3.…”
Section: Does the Platelet Ep3 Paradigm Apply To Human Platelets?mentioning
confidence: 99%
“…Thus, and as opposed to the action of EP3, EP2 and EP4 activation inhibit platelet aggregation [13] . However, the relative importance of this effect is unclear both in mice [13][14][15] and humans [13,14,[16][17][18][19][20] . Murine observations revealed that the impact of PGE2 on thrombosis, i.e.…”
Section: The Platelet Ep3 Paradigm In Micementioning
confidence: 99%